2010
DOI: 10.1099/mic.0.034298-0
|View full text |Cite
|
Sign up to set email alerts
|

Study of the distribution of autotrophic CO2 fixation cycles in Crenarchaeota

Abstract: Two new autotrophic carbon fixation cycles have been recently described in Crenarchaeota. The 3-hydroxypropionate/4-hydroxybutyrate cycle using acetyl-coenzyme A (CoA)/propionyl-CoA carboxylase as the carboxylating enzyme has been identified for (micro)aerobic members of the Sulfolobales. The dicarboxylate/4-hydroxybutyrate cycle using oxygen-sensitive pyruvate synthase and phosphoenolpyruvate carboxylase as carboxylating enzymes has been found in members of the anaerobic Desulfurococcales and Thermoproteales.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
92
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 67 publications
1
92
0
Order By: Relevance
“…On the other hand-and in line with the oxygen sensitivity of its ferredoxindependent carboxylase-the DC/HB cycle seems to be limited to anaerobic autotrophic species of the Thermoproteales and Desulfurococcales order (18,64,102). In contrast, the HP/HB cycle was found to operate in (micro)aerobic members of the Sulfolobales order, as well as in aerobic marine group I archaea ("Taumarchaeota") (16,18,19).…”
Section: Carboxylases In Autotrophic Pathwaysmentioning
confidence: 89%
“…On the other hand-and in line with the oxygen sensitivity of its ferredoxindependent carboxylase-the DC/HB cycle seems to be limited to anaerobic autotrophic species of the Thermoproteales and Desulfurococcales order (18,64,102). In contrast, the HP/HB cycle was found to operate in (micro)aerobic members of the Sulfolobales order, as well as in aerobic marine group I archaea ("Taumarchaeota") (16,18,19).…”
Section: Carboxylases In Autotrophic Pathwaysmentioning
confidence: 89%
“…Genomic studies of the Thaumarchaeota suggested a functioning HP/HB cycle (4,13,(19)(20)(21)(22), which was first identified in the thermophilic crenarchaeon Metallosphaera sedula (19) and was extended to other aerobic Crenarchaeota (14,23). Briefly, one acetyl-CoA and two bicarbonate molecules are converted via 3-hydroxypropionate to succinyl-CoA.…”
Section: Nitrosopumilus Maritimus | Autotrophymentioning
confidence: 99%
“…All six carbon fixation pathways known to date (Berg et al, 2010) were incomplete or undetectable in Fn1 (Supplementary Figure S5a). This latter feature is distinct from other sequenced thaumarchaeal and autotrophic crenarchaeal genomes (Berg et al, 2010;Beam et al, 2014;Konneke et al, 2014), further building on previous evidence which suggests a more versatile metabolism for members of the Phylum Thaumarchaeota (for example, bacterial ectosymbionts (Muller et al, 2010) and facultative ammonia oxidizers (Mussmann et al, 2011)). Fn1 is not predicted to ferment pyruvate to end products such as acetate, butyrate, ethanol, H 2 , lactate, and propionate (Supplementary Table S3).…”
mentioning
confidence: 99%